Incidence of ovarian cancer in the Central Hospital of the Police Forces Health - Vidal Amat y León, Jorge (2015)
The incidence of ovarian cancer in a General Hospital is presented, as is the Central Hospital of the Health of the Police Forces, making a study of all cases filed in the span of 25 years (1959-1983) diagnosed in the Department HCSFP Pathology. Of a total of 296.704 patients have been screened for cancer at the Department of Gynecology 647 cases of gynecologic cancer, 61 cases of ovarian cancer with an incidence of 9.5%, with 70% of advanced stays were diagnosed and 30% Started with a 5-year survival without disease 21.3%. Show the new approach to treating ovarian to be known throughout surgeon who ventures into the abdomen cancer.